2023
DOI: 10.3390/s23041779
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of Crop Type for Smallholder Farming Systems Using Deep Learning on Time-Series Sentinel-2 Imagery

Abstract: Climate change and the COVID-19 pandemic have disrupted the food supply chain across the globe and adversely affected food security. Early estimation of staple crops can assist relevant government agencies to take timely actions for ensuring food security. Reliable crop type maps can play an essential role in monitoring crops, estimating yields, and maintaining smooth food supplies. However, these maps are not available for developing countries until crops have matured and are about to be harvested. The use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Each sample point was located within at least a 10 m × 10 m area of a single crop type or a significantly dominant crop type, which was consistent with the spatial resolution of the satellite imagery used in this study (see Section 3.2). A total of 886 sample points were collected, predominantly consisting of major crop types, namely paddy rice (84), durian (57), eucalyptus (69), oil palm (85), pineapple (58), sugarcane (47), cassava (53), rubber plantation (82), mangosteen (29), and coconut (22). Additionally, samples were gathered for urban (61), water (40), forest (33), grass/shrub (39), bare ground (51), and others (76).…”
Section: Field Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Each sample point was located within at least a 10 m × 10 m area of a single crop type or a significantly dominant crop type, which was consistent with the spatial resolution of the satellite imagery used in this study (see Section 3.2). A total of 886 sample points were collected, predominantly consisting of major crop types, namely paddy rice (84), durian (57), eucalyptus (69), oil palm (85), pineapple (58), sugarcane (47), cassava (53), rubber plantation (82), mangosteen (29), and coconut (22). Additionally, samples were gathered for urban (61), water (40), forest (33), grass/shrub (39), bare ground (51), and others (76).…”
Section: Field Datamentioning
confidence: 99%
“…To date, most studies have focused on identifying individual crop types, such as sugarcane [43], mung bean [44], and paddy rice [45], with reported accuracies typically higher than 90%. Some other studies have attempted to map multiple, but limited numbers of, crop types (equal to or fewer than five) in one modeling framework (e.g., [46][47][48]). The reported accuracies were typically lower than mapping one single crop type, due to the similarity in phenology among the studied crops, making inter-class variation challenging to capture.…”
Section: Effectiveness Of Fine-scale Image Time Series In Tropical Cr...mentioning
confidence: 99%
“…The prior studies have demonstrated that incorporating vegetation features into the extraction of crop distribution information from remote sensing imagery can result in improved discrimination between vegetation and non-vegetation, as well as different types of vegetation, compared to relying solely on the original four spectral bands [36][37][38]. This study employed prior knowledge to extract four additional vegetation indices from the original four spectral bands, namely the Normalized Difference Vegetation Index (NDVI), Green Normalized Difference Vegetation Index (GNDVI), Optimal Soil Adjusted Vegetation Index (OSAVI), and Canola Index (CI) [17,39].…”
Section: Vegetation Featurementioning
confidence: 99%
“…Chandel et al [12] found that the combination of computer vision and thermal RGB images helped in the high-throughput mitigation and management of crop water stress. The method proposed by Khan et al [13] can be applied on a large scale to effectively map the crop types of smallholder farms at an early stage, enabling them to plan a seamless supply of food. There are also studies that use different methods to study the same crop.…”
Section: Introductionmentioning
confidence: 99%